2008
DOI: 10.3122/jabfm.2008.06.070267
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Diabetics with Poor Glycemic Control Who Achieve Good Control

Abstract: Objective: To find the characteristics of diabetics with poorly controlled diabetes that became well controlled compared with the patients with poorly controlled diabetes that remained poorly controlled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 16 publications
2
22
1
1
Order By: Relevance
“…However, other studies [37][38][39] found that diabetes knowledge, attitude and adherence to health regimens were associated with glycemic control. Lack of relationships among age and gender and poor glycemic control in our study is consistent with Shani et al [40] who found neither age nor gender were related to the achievement of good glycemic control. Moreira et al [41] found that gender was not associated with improved glycemic control.…”
Section: Hba1c <7supporting
confidence: 92%
“…However, other studies [37][38][39] found that diabetes knowledge, attitude and adherence to health regimens were associated with glycemic control. Lack of relationships among age and gender and poor glycemic control in our study is consistent with Shani et al [40] who found neither age nor gender were related to the achievement of good glycemic control. Moreira et al [41] found that gender was not associated with improved glycemic control.…”
Section: Hba1c <7supporting
confidence: 92%
“…Other studies have noted that there are age differences in patients who seek care from a single provider and those who do not develop continuous relationships with physician. 16 It is also possible that there are other differences that we did not measure that would obscure the benefits of a personal physician-patient relationship. For example, it is possible that patients who did not have a continuous provider were less ill than those who had a regular provider.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from being preventable, the majority of patients (194, 96%) had long standing T2DM (6 -10 years). Glycemic control is significantly associated with age, race/ethnicity, duration of diabetes, type and number of medications taken, obesity, psychological variables, and family support [52][53][54][55][56][57][58][59][60][61][62][63]. In addition, poor medical care, lack of education, non-compliance of patients or access to care problems all contribute to poor glycemic control, all of which are relevant to resource poor countries.…”
Section: Discussionmentioning
confidence: 99%